(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background: Ankle& foot surgeries are very common surgeries in various age groups like young & geriatric as well as in patients with comorbidities. Popliteal nerve block is one of multimodal Anaesthesia & analgesia for same. we have used ultrasound guided block to prevent complications &precise volume at a site for improving Characteristics of block. Aims of study: To study the technique of giving popliteal nerve blocks with ultrasonographic guidance and evaluate it in terms of: No of attempts, Time required for sensory and motor blockade, Quality of Intra operative analgesia, Duration for post-operative analgesia, Supplementation required in form of sedo analgesia/general anaesthesia & Complications encountered. Methods: We performed ultrasonography guided popliteal nerve block in 60 adult patients of ASA grade I/II/III undergoing foot and ankle surgeries. The volume of drug used was 20ml consisting of Lignocaine (1.5%) 10ml and Bupivacaine (0.5%) 10ml; Results: The mean time taken to conduct the block was 4.3±1.4 mins. The mean time taken for sensory onset was 3.8±1.1 mins. The mean time taken for motor onset was 7.0± 1.4 mins. The mean time taken for completing the surgery was 39.2±5.0 mins. The mean time taken for complete motor regression was 143.8±13.5 mins. The mean time taken for complete sensory regression was 184.8± 16.8 mins. The patients first complained of pain at the mean time of 239±22.4 mins. The patients have stable haemodynamic parameters: pulse rate, SBP, DBP throughout the operation. Failure of block was seen in 4 patients where supplementation in the form of Injection Midazolam 1mg IV and Injection Fentanyl 50microgm IV was given in 2 patients and general anaesthesia was given in 2 patients. No other neurological complications were noticed in our study. Conclusion: ultrasound guided Popliteal nerve block is safe& effective block for various ankle &foot surgeries.